Rehabilitation Methods of Rasuna Said House in Agam Regency, West Sumatra - Riki Adriadi; I Nengah Tela; Jonny Wongso (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Efforts to preserve buildings, especially cultural heritage buildings, can be carried out in various ways depending on the type of damage to the building. Likewise, the damage to the building is caused by many factors, and if the cause of the damage is known, then it is necessary to find out how to carry out rehabilitation/treatment that is most appropriate to the type of damage that occurred. Meanwhile, in Indonesia, the manual for repairing cultural heritage buildings does not yet have the same standard. For this reason, research is needed to determine how to rehabilitate cultural heritage buildings, because the way the work is done has a different method from buildings in general. Rasuna Said's house is one of the cultural heritage buildings located in Agam Regency, West Sumatra Province. Historically, this building was once the home of Hj. Rasuna Said, a well-known National Hero who was persistent in fighting for the independence of the Indonesian people during the Dutch colonial period. To honor his struggle and preserve the history of this house building, in 2017 the Government has designated Rasuna Said's house as a National Rank cultural heritage by decree of the Minister of Education and Culture Number 370/M/2017 [1]. Tela (2021), stated that from the results of previous research, regarding Rasuna Said's house, it was stated that this house suffered a lot of damage, both on the roof, roof wood frame, and building walls. Therefore, to follow up on the results of the research, the researcher considers it necessary to conduct research on the work method of repairing damage to the cultural heritage building of Rasuna Said's house in Agam Regency, West Sumatra. This research is devoted to examining the method of repairing architectural components. Because the building of Rasuna Said's house based on the results of previous research, damage occurred to architectural components consisting of roofs, ceilings, walls, windows, doors and floors of the building. By using the method of collecting data through field observations/observations and the desk study method, namely the method of collecting data and information through the study and analysis of data and information using secondary data, either in the form of reports, references, photos and maps. The analysis that will be carried out is data processing to produce a plan document for the rehabilitation of cultural heritage buildings by considering the data from measurements, descriptions, identification, photography and research that has been carried out. This rehabilitation method is to obtain results that are in accordance with the initial building, both in terms of form, material and the way the rehabilitation works. The results of this study are the basis for the preparation of a building improvement plan which includes the concept of improvement and recommendations on how to carry out repairs to the Rasuna Said house as a cultural heritage building.